Applying global NASA data to local planning for extreme heat in Prince George’s County, Maryland - Schollaert Uz, Stephanie; Stover, Katharine C.; Smith, Samantha L.; Collier, Debra M.; Riley, Jacob; Hoban, Evelyn H. (Frontiers in Environmental Science, 2025)
As demand grows for high-quality public information around the increasing societal impacts of extreme weather, making scientific data products more actionable for practitioners has become a top priority for NASA. In early 2024, several of us from NASA Goddard Space Flight Center began collaborating with Prince George’s County, Maryland staff to apply space-based observations to help inform local decisions around building resilience to environmental stressors. Prince George’s County is home to Goddard Space Flight Center hosting a comprehensive array of Earth observing satellite and modeling products and expertise to advance understanding of Earth as a system, providing critical long-term data records over space and time. Scientific and academic communities have primarily used these global data products to advance fundamental understanding of Earth processes and their changes, rather than informing practical decisions. Here we describe a demonstration to bridge that gap, initially around reducing exposure of humans to extreme heat. Working with agency staff from the Prince George’s County Department of Environment and the Prince George’s County Health Department, NASA shared satellite-derived land surface temperatures from Aqua-MODIS and Landsat as well as land cover classifications to analyze seasonal temperature trends with land use changes over the past few decades. Prior to partnering with NASA, the county was using sparse in situ temperature records, extremely valuable and essential for ground-truthing satellite data, but limited spatially and temporally. The addition of space-based data augments these few ground-based measurements with a broad view of spatial and temporal temperature trends that can be layered with additional county data to help identify areas of increased heat with land use change patterns. We also compared the temperature trends to records of annual heat-related emergency room visits. By combining environmental data with local health impacts, the County plans to pinpoint heat-related vulnerability patterns over time. This unique combination of global and local data serves to pilot science-based criteria to inform and prioritize projects and programs to reduce heat exposure of Prince George’s County’s workers and residents.